Effect of yttria on gas sensitivity of tungsten trioxide - Shahrokh Abadi, Mohammad Hadi; Hamidon, Mohd. Nizar; Wagiran, Rahman; Shaari, Abdul Halim; Misron, Norhisam; Abdullah, Norhafizah (International Frequency Sensor Association Publishing, 2009)
The influence of 5, 10, and 15 wt % of yttrium oxide on gas sensitivity of tungsten oxide was studied. The prepared powders were mixed with a binder and printed onto the electrode surface using thick-film screen printing. Microstructure, electrical conductivity, and gas sensitivity of films were dependant on the ratio of doped yttria, and thickness of the film. Increasing the ratio of yttria beyond 10 wt % causes a deficient electrical conductivity and very low sensitivity of the films when they exposed to the organic solvent. Higher sensitivity to the solvents was observed at 10 wt % of doping in both thickness of 7 and 15 µm. Selectivity, response time, and thermal dependency of responses to the solvents were compared with a commercial alcohol sensor.